IGFBP2 and IGFBP4 interact to activate complement pathway in diabetic kidney disease - Jieling Liang; Yangxiao Huang; Daping Peng; Yali Xie; Yifei Liu; Xiuxia Lu; Junfa Xu (Renal Failure)
Background Diabetic kidney disease (DKD) is the leading cause of chronic kidney disease globally. Recent research has identified insulin-like growth factor-binding proteins 2 (IGFBP2) and 4 (IGFBP4) as potential biomarkers for DKD. Overactivation of the complement pathway in DKD remains poorly understood.Methods Blood samples were collected from patients for proteomic analysis, complemented by both in vitro and in vivo experiments to investigate the roles of IGFBP2, IGFBP4, and the complement pathway in DKD.Results Elevated levels of IGFBP2 and IGFBP4 were observed in DKD patients. The levels of IGFBP2 and IGFBP4 increased in DKD mice, accompanied by the activation of the complement pathway, and a deterioration in renal function. High glucose and serum from DKD mice stimulated an increase in the levels of IGFBP2 and IGFBP4 in HK-2 cells. The supernatant from HK-2 cells was used to culture THP-1 cells, resulted in an increase in the M1 type of THP-1 cells, a decrease in the M2 type, and activation of the complement pathway. The supernatant from THP-1 cells affected the growth of primary human renal podocytes. The exogenous addition of IGFBP2 and IGFBP4 proteins to primary human renal podocytes did not affect their growth. However, when human renal podocytes were cultured with the supernatant from THP-1 cells, the growth of the podocytes was affected.Conclusions IGFBP2 and IGFBP4 interact to stimulate the activation of the complement pathway in macrophages, which induces podocyte apoptosis and subsequently promotes the development of DKD.